2016
DOI: 10.4184/asj.2016.10.2.366
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Objective Physical Activity Measurements using a Wireless Accelerometer Following Minimally Invasive Transforaminal Interbody Fusion Surgery

Abstract: We report on a case of a patient who underwent minimally invasive transforaminal lumbar interbody fusion (mi-TLIF) with objective physical activity measurements performed preoperatively and postoperatively at up to 12-months using wireless accelerometer technology. In the first postoperative month following surgery, the patient had reduced mobility, taking 2,397 steps over a distance of 1.8 km per day. However, the number of steps taken and distance travelled per day had returned to baseline levels by the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The current study findings showed a significant decrease in disability levels in the second and third months in the intervention group compared with the control group. This finding is consistent with previous study results (Can et al, 2010; Jakobsson et al, 2019; Mobbs et al, 2018; Phan & Mobbs, 2016). Whereas some authors reported that exercise programs starting 4 to 6 weeks after surgery caused rapid decreases in pain and disability (Ostelo et al, 2009), other authors reported that although the effects of early activity on pain may be felt sooner, the effects on functional capacity would emerge later (Ozkara et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study findings showed a significant decrease in disability levels in the second and third months in the intervention group compared with the control group. This finding is consistent with previous study results (Can et al, 2010; Jakobsson et al, 2019; Mobbs et al, 2018; Phan & Mobbs, 2016). Whereas some authors reported that exercise programs starting 4 to 6 weeks after surgery caused rapid decreases in pain and disability (Ostelo et al, 2009), other authors reported that although the effects of early activity on pain may be felt sooner, the effects on functional capacity would emerge later (Ozkara et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Pain and disability can be prevented in the early post‐operative period after lumbar hernia surgery through appropriate care and rehabilitation (den Boer et al, 2006). However, the number of studies in the literature on the effectiveness of walking after LDH surgery and its use as an intervention strategy is limited (Mobbs et al, 2016, 2018; Phan & Mobbs, 2016). In light of this information, the aim of this study was to evaluate the effect of pedometer‐supported walking and telemonitoring on patients' pain, disability and quality of life after LDH surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Objective monitoring of activity and Gait Velocity using wearable accelerometer following lumbar microdiscectomy to detect recurrent disc herniation walking performance; used in conjunction with the walking test (10,11). There have been multiple case studies on the effectiveness of wearable accelerometers post spinal surgery, for instance recovery post minimally invasive fusion (9). The first clinical series using accelerometers for monitoring post spinal surgery recovery was published in 2016 (12).…”
Section: Case Reportmentioning
confidence: 99%
“…Traditionally, quantification and comparison of recovery or outcomes in patient's post-spinal procedures used subjective rating scores such as Oswestry Disability Index (ODI), Visual Analogue pain Scale scores (VAS), Short Form Health (SF-12, SF-36) survey scores amongst a variety of others (6)(7)(8). However, the major problem in utilizing these scores is their subjectivity and the inherent bias with self-appraisal, as different individuals perceive and tolerate pain differently (9). Recent literature states that the ODI should not be a stand-alone tool for evaluating walking limitation in patients with lumbar spinal stenosis (10).…”
Section: Introductionmentioning
confidence: 99%
“… 4 We have also shown in a case report 12-month follow-up of using an accelerometer to collect distance and walking data, which is feasible and easily managed by the patient. 7 The available preliminary data holds promise for objective functional measures in the context of spinal conditions and spine surgery, but further studies are required to determine the optimal tool for objective evaluation of functional impairment.…”
mentioning
confidence: 99%